2020
DOI: 10.1523/eneuro.0061-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Differential Rapid Plasticity in Auditory and Visual Responses in the Primarily Multisensory Orbitofrontal Cortex

Abstract: Given the connectivity of orbitofrontal cortex (OFC) with the sensory areas and areas involved in goal execution, it is likely that OFC, along with its function in reward processing, also has a role to play in perceptionbased multisensory decision-making. To understand mechanisms involved in multisensory decision-making, it is important to first know the encoding of different sensory stimuli in single neurons of the mouse OFC. Ruling out effects of behavioral state, memory, and others, we studied the anestheti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…Cross-modal enhancement appears not to be the default integrative mode for mPFC neurons of awake rats because most of them failed to show it in the choice-free task (Task 3). Similar results were found in other studies [67][68][69]. However, this result is quite different from earlier studies conducted in the superior colliculus and other sensory cortical areas that primarily showed enhanced multisensory responses to spatiotemporally congruent cues [3,4,70,71].…”
Section: Discussionsupporting
confidence: 63%
“…Cross-modal enhancement appears not to be the default integrative mode for mPFC neurons of awake rats because most of them failed to show it in the choice-free task (Task 3). Similar results were found in other studies [67][68][69]. However, this result is quite different from earlier studies conducted in the superior colliculus and other sensory cortical areas that primarily showed enhanced multisensory responses to spatiotemporally congruent cues [3,4,70,71].…”
Section: Discussionsupporting
confidence: 63%
“…We found that most units responded robustly to the auditory stimulus and of these, ∼73% did not respond to the visual stimulus. Based on the latency of peak response to visual and auditory stimulus and the post-hoc Nissl staining of the sliced brain (Sharma and Bandyopadhyay, 2020), we claim that all of our electrodes were in the ACX. Thus, we claim the existence of inhibitory and excitatory neurons in layer 5/6 of the ACX as potential direct and indirect source that may drive hyperpolarization of neurons in layer2/3.…”
Section: Resultsmentioning
confidence: 97%
“…This percent can be explained by AuD’s proximity with secondary visual areas. AuD previously has been shown to be multisensory, responding to both auditory and visual stimuli (Sharma and Bandyopadhyay, 2020). Another point to notice here is that in the type MAV population, not all cells showed significant change on multisensory presentation (85%) and all those that did majority of them showed suppression (Fig.5A, Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations